Celiac plexus block - Brown, David (Henry Stewart Talks, 2009)
Anatomy, Demographics of pancreatic cancer pain, US cancer deaths, Relative survival, Pancreatic cancer risk factors, Pancreatic cancer pain, Retrocrural anatomy and pancreatic cancer, Celiac Technique, Neurolytic celiac plexus block in cancer pain: a meta-analysis, Block outcome, Managing risks of technique